Description of Triglyceride Levels in Type 2 Diabetes Mellitus Patients at Hospitals Dr. H. Moch. Ansari Saleh Banjarmasin 2023 - Hefjatun Amalia; Rizki Perdani; Wulan Pratiwi (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
T2DM is a condition characterized by increased blood glucose levels due to metabolic disorders caused by a lack of the hormone insulin. The condition affects the body's use of sugar as an energy source, due to the malfunction of the insulin hormone and this also causes disturbances in lipid metabolism, which is characterized by an increase in lipid derivatives such as TG. TG is fat found in the bloodstream which functions as an energy source. The normal value for TG levels according to Ahmad (2023) is <150 mg/dl. The aim of this study was to determine the description of TG levels in T2DM patients based on gender and age group. The type of research is descriptive quantitative with a cross sectional method. This research used a total sampling of 119 based on RM data at RSUD dr. H. Moch. Ansari Saleh Banjarmasin in 2023. Based on research results, the highest number of TG level cases were in the high TG level category (200-499 mg/dl) as much as 41%, the majority of the increase was in women with the highest TG level category (200-499 mg/dl), namely 46%, and based on age group, the most cases were in the late elderly (55-65 years) with the highest TG level category (200-499 mg/dl) namely 15%.